2017
DOI: 10.3390/molecules22030394
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of LCB 01-0648, a Novel Oxazolidinone, against Gram-Positive Bacteria

Abstract: Oxazolidinones are a novel class of synthetic antibacterial agents that inhibit bacterial protein synthesis. Here, we synthesized and tested a series of oxazolidinone compounds containing cyclic amidrazone. Among these compounds, we further investigated the antibacterial activities of LCB01-0648 against drug-susceptible or resistant Gram-positive cocci in comparison with those of six reference compounds. LCB01-0648 showed the most potent antimicrobial activities against clinically isolated Gram-positive bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Because LCB01-0699 showed less bone marrow toxicity ( Figure 4 ), LCB01-0699 is considered a potential antibacterial candidate, with high activities and low toxicity. While our previous study provided in vitro activities of LCB01-0648 against Linezolid -resistant S. aureus or other Gram-positive cocci [ 13 ], we did not provide in vivo activity of LCB01-0699 against Linezolid -resistant S. aureus or other Gram-positive cocci. Therefore, further in vivo analyses should be carried out to better understand the antibacterial activity of LCB01-0699 against multi-drug resistant Gram-positive cocci, including Linezolid -resistant S. aureus .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Because LCB01-0699 showed less bone marrow toxicity ( Figure 4 ), LCB01-0699 is considered a potential antibacterial candidate, with high activities and low toxicity. While our previous study provided in vitro activities of LCB01-0648 against Linezolid -resistant S. aureus or other Gram-positive cocci [ 13 ], we did not provide in vivo activity of LCB01-0699 against Linezolid -resistant S. aureus or other Gram-positive cocci. Therefore, further in vivo analyses should be carried out to better understand the antibacterial activity of LCB01-0699 against multi-drug resistant Gram-positive cocci, including Linezolid -resistant S. aureus .…”
Section: Discussionmentioning
confidence: 94%
“…Previously, we reported that LCB01-0648 had potent in vitro activity and minimal safety issues [ 13 ]. To examine whether LCB01-0699 was really converted to LCB01-0648 in vivo, a pharmacokinetic study was conducted in a rat model system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LegoChem Biosciences, Inc. (Daejeon, South Korea) has developed several oxazolidinone derivatives as antibacterial agents in the last decade. 32–35 For example, compound 13 (LCB01-0062) (Fig. 2) showed in vitro activity against clinical isolates of Gram-positive bacteria compared to several antibacterial drugs, including linezolid, erythromycin, ciprofloxacin, and vancomycin.…”
Section: Oxazolidinones As Antibacterial Agentsmentioning
confidence: 99%